New one-dimensional mercury(II) coordination polymers built up from dispiro-dipyridyloxy-cyclotriphosphazene: Structural, thermal and UV–Vis absorption properties. (15th March 2019) - Davarcı, Derya; Tümay, Süreyya Oğuz; Şenkuytu, Elif; Wörle, Michael; Zorlu, Yunus
Graphical abstract: New two mercury(II) cyclotriphosphazene coordination polymers were synthesized and their crystal structures, thermal behaviours and UV properties were determined. Abstract: Reactions of flexible polydendate ligand system dispiro-dipyridyloxy-cyclotriphosphazene (L ) with a variety of mercury(II) salts (HgX2 ) (X = I −, Cl − ) afforded two one-dimensional mercury(II) coordination polymers, namely formulated as [Hg(L)(I)2 ]n (1 ) and [Hg(L)(Cl)2 ]n .(ACN)0, 341 (2 ). The isolated crystalline compounds were structurally characterized by single crystal X-ray crystallography. The X-ray crystal structure analysis revealed that1 and2 crystallizes in the orthorhombic (space group Pccn ) and the monoclinic crystal system (space group P 21 /c), in whichL exhibited a κ 2 N coordination binding mode with the divalent Hg ions to form one-dimensional chain structures. The central Hg 2+ ion in1 and2 has a distorted tetrahedral coordination geometry. UV–Vis properties and thermal stability ofL and complexes (1, 2 ) were also investigated. UV–Vis experiments (titration and continuous variation (Job's plot) analysis) showed that all of spectrophotometric properties in solution state supports crystal structure of complexes. According to TGA analysis, coordination polymers exhibited thermal stability up to 300 °C, butL showed more thermal stability than1 and2 .